2021
DOI: 10.1002/14651858.cd011672.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant therapy via thin catheter in preterm infants with or at risk of respiratory distress syndrome

Abstract: Surfactant therapy via thin catheter in preterm infants with or at risk of respiratory distress syndrome (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 78 publications
3
89
0
1
Order By: Relevance
“…A meta-analysis found LISA to be associated with lower BPD incidence at 36 weeks' PMA and the incidence of the composite outcome of death or BPD at 36 weeks' PMA compared to conventional surfactant administration via intubation ( 44 ). Similar results were noted in the recent Cochrane review by Abdel-Latif et al (BPD-relative risk (RR): 0.57; 95% CI: 0.45–0.74; death-RR: 0.63; 95% CI: 0.47–0.84; combined BPD or death-RR: 0.59, 95% CI: 0.48–0.73) ( 45 ).…”
Section: Medications Used In Bpdsupporting
confidence: 86%
“…A meta-analysis found LISA to be associated with lower BPD incidence at 36 weeks' PMA and the incidence of the composite outcome of death or BPD at 36 weeks' PMA compared to conventional surfactant administration via intubation ( 44 ). Similar results were noted in the recent Cochrane review by Abdel-Latif et al (BPD-relative risk (RR): 0.57; 95% CI: 0.45–0.74; death-RR: 0.63; 95% CI: 0.47–0.84; combined BPD or death-RR: 0.59, 95% CI: 0.48–0.73) ( 45 ).…”
Section: Medications Used In Bpdsupporting
confidence: 86%
“…Multiple studies have interrogated thin catheter administration of surfactant. A Cochrane review concluded that the thin catheter method was superior to endotracheal tube surfactant administration 3 . However, the majority of included studies enrolled subjects of GA >28 weeks at low risk of developing BPD.…”
Section: Commentarymentioning
confidence: 99%
“…It was found that the LISAtreated infants scored higher on the psychomotor development index (PDI) and mental development index (MDI) [125]. With the recently published Cochrane review, in which the administration of surfactant via thin catheter compared with the administration via an endotracheal tube was found to significantly reduce the risk of death or BPD, intubation in the first 72 h of life, severe IVH, BPD in survivors as well as in-hospital mortality [126], and the pending results of the OPTIMIST-A trial, it is anticipated that the clinical use less invasive surfactant administration will be expanded.…”
Section: Less Invasive Surfactant Administration/minimal Invasive Surfactant Techniquementioning
confidence: 99%